Pancasila as an Ethical System - Stefany Dian Nugraheni; Victorya Angel; Vika Herta Puspita; Widya Nirmala Santi; Riska Andi Fitriono (Journal of Education Technology Information Social Sciences and Health, 2022)
Pancasila and Ethics are two things that cannot be separated, remember that in both Pancasila and Ethics both contain and teach each other good values. Pancasila ethics is a behavior to regulate life society, nation and state which has a fundamental assessment according to view of the values of Pancasila, namely the values of democracy, the values of justice, and the values of unity. An activity or deed can be said to be good not only if it is not neglected the values of Pancasila, but how to practice the characteristics of Pancasila which there has become something that can provide more benefits for others. Although the values in Pancasila are a form of value crystallization process who live in a social reality, customs and religion, however actually Pancasila also has a universal nature so that it can be recognized by anyone anywhere and anytime. Pancasila Ethics discusses very essential qualities in human existence. Implementing one of the Pancasila values is not enough, because Pancasila is a system of values that cannot be separated from one another each other. Therefore, Pancasila is used as a moral formation and implemented in the life of society, nation and state. Effective implementation of Pancasila values can be done through education and social media. Education can be supported through formal education in the school environment, informal in the family environment, and non-formal in the community environment. Meanwhile, through social media, the media must have a vision and mission which can build and educate the character of society to think forward with Indonesian personality